UPAYA LEMBAGA PENDIDIKAN DALAM MENGIMPLEMNTASIKAN NILAI-NILAI KARAKTER UNTUK MEMBENTUK AKHLAK PESERTA DIDIK DI MA AL-MUHAJIRIN TUGUMULYO - Nindi Tri Handayani; Septi Dwi Lestari; Nadya Fajrika (CV. ALIM'SPUBLISHING, 2023)
The existence of this research is because there are many students whose morals are not good. This study aims to describe the efforts of educational institutions in implementing character values ​​to shape the morals of students and also the obstacles experienced by educational institutions in implementing character values. The results of the research show that: First, the efforts of educational institutions in instilling religious character in students so that they have morals towards Allah SWT, parents and teachers. Then the efforts of educational institutions in instilling the character of discipline in students so that they are disciplined towards Allah SWT, parents and teachers. In addition, there are also efforts by educational institutions to implement the character values ​​of the responsibilities of students so that they have a sense of responsibility towards Allah SWT, parents and teachers. Second, the obstacles of educational institutions in implementing character values ​​to shape the morals of students include students whose character has been formed from before school which is difficult to change and the lack of role of parents in guiding children at home due to busy parents at work.